Understanding energy cultures of space heating in Aotearoa New Zealand: a desktop review of slow ground source heat pump uptake - Analiese Barr; Smrithi Talwar (Kōtuitui)
This paper examines the slow adoption of geothermal Ground Source Heat Pump (GSHP) technology in New Zealand amid the urgent need for sustainable energy solutions in the face of the climate crisis. Internationally, GSHPs offer many environmental, social and economic benefits across residential and commercial sectors. However, despite the global installation of approximately 6.5 million GSHP units, New Zealand has seen limited implementation, with 130 known installations. Using the Energy Cultures Framework, this paper conducts a scoping literature review to analyse the dominant socio-economic barriers to GSHP uptake including energy hardship, prioritisation of immediate savings over long-term cost-saving benefits, low public awareness and financial risk aversion towards new sustainable energy solutions. This paper recommends further industry engagement and primary research to understand New Zealand's heating norms and attitudes towards GSHPs. Additionally, this paper advocates for future cost–benefit analysis to evaluate GSHP's potential contributions to decarbonisation objectives, alleviating electricity system pressures, and mitigating energy hardship. Such future analysis may serve as a catalyst for stimulating future uptake of GSHP technology.